2022
DOI: 10.25259/jcis_51_2022
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing low contrast volume thoracic CT angiography: From the basics to the advanced

Abstract: Contrast-enhanced CT angiography (CTA) is a widely used, noninvasive imaging technique for evaluating cardiovascular structures. Contrast-induced nephrotoxicity is a concern in renal disease; however, the true nephrotoxic potential of iodinated contrast media (CM) is unknown. If a renal impaired patient requires CTA, it is important to protect the kidneys from further harm by reducing total iodinated CM volume while still obtaining diagnostic quality imaging. These same reduced volume CM techniques can also be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…This is thought to be primarily influenced by the injection rate rather than injection volume. [ 1 , 8 ] The more rapid the delivery of a fixed contrast dose, the faster contrast accumulates in the aorta leading to greater aortic opacification. Prior studies have also reported no significant difference in arterial phase liver enhancement with varying IV contrast doses.…”
Section: Discussionmentioning
confidence: 99%
“…This is thought to be primarily influenced by the injection rate rather than injection volume. [ 1 , 8 ] The more rapid the delivery of a fixed contrast dose, the faster contrast accumulates in the aorta leading to greater aortic opacification. Prior studies have also reported no significant difference in arterial phase liver enhancement with varying IV contrast doses.…”
Section: Discussionmentioning
confidence: 99%
“…We performed a Web of Science Core Collection search for the keywords ‘iodinated contrast media shortage’, and we found 14 scientific papers, 1,2,9–20 and 1 editorial, 21 all published in 2022. Almost all these papers were published by authors from the USA or Australia; the one exception was a paper with mixed authorship from Germany, Switzerland, and the USA 9 .…”
mentioning
confidence: 99%